(untitled) - Henry, Anthony (Oxford,New York, 2008)
Designed specifically for modules taught over one semester, this new textbook covers all the core topics of Strategic Management in 12 manageable chapters. This succinct textbook takes students through all the key stages of Strategic Management: Analysis, Formulation, and Implementation, with an emphasis on providing students with the tools of analysis essential for understanding the competitive and internal environments that organisations face. Classic subjects such as Industry Analysis and Strategic Leadership are thoroughly investigated, as well as contemporary ideas on Corporate Governance and Globalization.
Keywords: Quản lý điều hành,Management,Lập kế hoạch chiến lược,Strategic planning